Apparent digestibility of Asian carp‐ and common carp‐derived fish meals in feeds for hybrid striped bass Morone saxatilis ♀ × M. chrysops ♂ and rainbow trout Oncorhynchus mykiss. (7th April 2014) - Bowzer, J.; Trushenski, J.; Rawles, S.; Gaylord, T.G.; Barrows, F.T.
Abstract Apparent digestibility coefficients (ADCs) of nutrients (crude protein, amino acids, crude lipid, fatty acids, and minerals) were determined for fish meals derived from menhaden, Asian carp (combination of silver and bighead carps), and common carp in feeds for hybrid striped bass and rainbow trout. Extruded test diets were formulated to contain a 70 : 30 mixture of reference diet and test ingredient with yttrium oxide (1 g kg−1) serving as the inert marker. Diets were randomly assigned to triplicate tanks and fish were fed once per day at 2% body weight. Fecal samples were collected by manual stripping. The ADCs were calculated according to standard procedures. The composition and digestibility of Asian carp and common carp meals was broadly similar to menhaden meal. Protein digestibility ranged from 86.5% (Asian carp meal) to 93.1% (common carp meal). Lipid was highly digestible with ADCs >100% for all ingredients. Although the Asian carp meal was less digestible than the other two fish meals, it was still a highly digestible ingredient. Our data suggest that fish meals derived from Asian or common carp would be valuable feedstuffs in diets for hybrid striped bass, rainbow trout, and possibly other cultured fishes.